BIOGEOGRAPHY OF INDONESIAN FRESHWATER FISHES: CURRENT PROGRESS - Arief Aditya Hutama; Renny Kurnia Hadiaty; Nicolas Hubert (Treubia, 2016)
Southeast Asia is one of the most geologically complex tropical regions on Earth, in which the intricate interactions among plate tectonics, volcanism and Pleistocene climatic fluctuations led to complex patterns of species distribution. An increasing number of biogeographic studies of the Indonesian ichthyofauna have already partially uncovered the potential mechanisms at the origin of present day species distribution. These studies are currently scattered in the literature and the present review aims at presenting recent progress. Here, we propose a review of this literature with the aim to provide a broad overview of the current progress in the field of Indonesian freshwater fishes biogeography. First, we will briefly present the geology of the Indo-Australian Archipelago (IAA) and highlight the time frame of the geographical settlement of the Indonesian archipelago. Second, we will present the palaeoecological history of Sundaland during the Pleistocene. Finally, we will present the results of recent biogeographic studies across the three biogeographic provinces (Sundaland, Wallacea, Sahul) and discuss how these results fit with geological and palaeoecological scenarios in Indonesia.